(3cJGH GdeaQhVGJs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3Cf fbSe NW CH KdGK CbSGe Ydi Cf jchf eQHYkG GdWQajf eSGhjjf deQHY GdhSW s
(3BNQgG (B:s
(3hLejY C O eYdhe hPdc eG CQOfGg JeJ GdeaQhVGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS YTQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1461s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs